Evaluation of flurbiprofen in detrusor instability. Issue 6210 (2nd February 1980) - Cardozo, L D; Stanton, S L; Robinson, H; Hole, D
Abstract : Thirty women with detrusor instability (27 cases idiopathic, and three secondary to multiple sclerosis) completed a double-blind, cross-over trial of the prostaglandin synthetase inhibitor flurbiprofen and a placebo, results being evaluated by questionnaire and cystometry. Frequency, urgency, and urge incontinence were all significantly reduced with flurbiprofen (P less than 0.001, P less than 0.025, and P less than 0.025 respectively), as was the detrusor-pressure rise during bladder filling (P less than 0.01). Side effects, however, occurred in 13 patients while taking flurbiprofen compared with five while taking placebo (P less than 0.025). After the trial 19 patients wished to continue with flurbiprofen. Flurbiprofen is a useful treatment for idiopathic detrusor instability and is well tolerated by most patients.